A Technique For Lock-In Prediction On A Fluid Structure Interaction Of Naca 0012 Foil With High Re - Arini, Nu Rhahida; Turnock, Stephen R.; Tan , Mingyi (EMITTER International Journal of Engineering Technology, 2020)
A numerical lock-in prediction technique of a NACA 0012 hydrofoil, immersed in a flow having a Re of 3.07x106 is proposed in this paper. The technique observes the foil’s response as part of a fluid-structure interaction analysis. The response is modelled by foil’s vibration which is represented by spring and damper components. The technique identifies and predicts the foil’s lock-in when it vibrates. The prediction is examined using the Phase Averaged Method which employs the Hilbert Transform Method. The aim of this paper is to propose a numerical way to identify a lock-in condition experienced by a NACA 0012 foil in a high Reynolds number flow. The foil’s mechanical properties are selected and its motions are restricted in two modes which are in the pitch and heave directions. The rotational and transverse lock-in modes are identified in the model. The existence of lock-in is verified using pressure distribution plot, the history of trailing edge displacement and fluid regime capture. The history of total force coefficients is also shown to justify the result. The result shows that the technique can predict reliably the lock-in condition on the foil’s interaction. Three main fluid induced vibration frequencies are generated in the interaction. None of them are close to natural frequency of the foil and lock-in is apparently not found in the typical operational condition.